1988
DOI: 10.1148/radiology.169.1.3420282
|View full text |Cite
|
Sign up to set email alerts
|

Advanced primary breast cancer: assessment at mammography of response to induction chemotherapy.

Abstract: The response to induction chemotherapy is an important prognostic factor in patients with nonmetastatic, locally advanced breast carcinomas. Assessment at mammography of the response of 60 breast cancers in 59 women was performed between 1974 and 1986. Responses were excellent in 13 tumors, moderate in 34, and poor in 13 (excellent moderate = 78%). Assessment of response of discrete masses in a fatty breast was easiest; assessment of response of tumor areas that were poorly defined-such as a focal area of arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 0 publications
0
59
0
4
Order By: Relevance
“…Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988). We also found that similar factors together with the presence of extensive DCIS limited to the interpretation of the MRI scans.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988). We also found that similar factors together with the presence of extensive DCIS limited to the interpretation of the MRI scans.…”
Section: Discussionmentioning
confidence: 69%
“…There is a poor correlation between the histological appearances of the tumour and measurements obtained by physical examination, mammography (MM) or ultrasonography (USS). Radiological assessment is least accurate in younger women who most often desire BCS because their breast tissue is more dense making it more difficult to distinguish invasive cancer from residual in situ carcinoma and chemotherapy-induced fibrosis (Cocconi et al, 1984;Segel et al, 1988, Vinnicombe, 1996.…”
mentioning
confidence: 99%
“…2 Mammography has been used widely for breast cancer screening, but it is difficult to diagnose breast cancers for breasts with high mammographic density and/or micro-calcifications. 3 Ultrasound imaging has higher sensitivity than mammography in imaging dense breast but with low specificity in screening breast cancers. 4,5 Magnetic resonance imaging (MRI) was reported to have results correlated better with pathology findings than mammography and obtained promising results when dynamic contrast agents are applied.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques assess therapeutic effects by either over-or underestimating the extent of residual disease due to fibrosis or sampling error (2,6,(11)(12)(13)(14)(15)(16). Although histology is the gold standard, the histological correlation of response with all of the above-mentioned modalities is not satisfactory.…”
mentioning
confidence: 99%